The Journal of Contemporary European Research (JCER) JCER is an open-access journal published by UACES in association with the UACES Graduate Forum. (2012)
JCER is an open-access journal published by UACES in association with the UACES Graduate Forum. We invite submissions from scholars who are experts in any subject area delivering analysis that relates to Europe. This includes, but is not limited to, P
olitics/International Relations, Area Studies, European Integration, Economics, Law, History, Culture and Learning & Teaching. The journal publishes the work of established academics alongside that of PhD students and early career researchers.